Evaluation of the Effectiveness of Using the CFTR Modulator Ivacaftor/Lumacaftor in Children with Cystic Fibrosis in the Sverdlovsk Region (Prospective Cohort Study) - Yuliya O. Vasenyova; Irina V. Vakhlova; Oleg Yu. Averyanov (Union of pediatricians of Russia, 2024)
Background. A modern achievement in the treatment of cystic fibrosis has been the discovery of small molecules that restore the processes of synthesis, transport to the membrane, and the work of the defective CFTR protein. Drugs whose action is aimed at restoring the function of the CFTR protein are called CFTR modulators. The aim of the study is the conduction of a comprehensive assessment of the effectiveness of CFTR modulator ivacaftor/lumacaftor therapy in children with cystic fibrosis based on the study of clinical, laboratory, and instrumental data. Methods. CFTR modulator ivacaftor/lumacaftor was received for 12 months by 23 children of the main group aged 2-17 years, who are homozygous carriers of the F508del mutation of the CFTR gene in the absence of the L467F complex allele. A control examination of the main group was conducted at the start of the study and then every 3 months for 12 months of drug administration. Results. The condition of the patients in the observation groups at the start of the study was assessed as moderate to severe, the bronchopulmonary process was in the stage of incomplete clinical remission. In the main group, the level of aspartate aminotransferase significantly decreased, in the control, on the contrary, there was a tendency for this indicator to increase. The level of alkaline phosphatase (alkaline phosphatase) decreased and reached normal in the main group; the relative risk of hyperphosphatasemia during treatment decreased by 5 times (0.187 (0.063-0.557)). The level of gamma-glutamyltranspeptidase (gamma-GTP) and the number of patients with elevated GGTP decreased (24.65 and 19.69 IU/l, respectively; 61 and 13%). In the control group, the level of gamma-GTP increased and the alkaline phosphatase did not normalize. The indicators of forced exhalation volume in the first second and forced vital capacity of the lungs were initially lower in the main group, after 12 months the differences remained. There was a tendency to decrease the frequency of severe pancreatic insufficiency in the main group by 17.3%, and no changes in the control group. Sweat chlorides tended to decrease in the main group in the absence of reaching the standard values. Conclusion. The usage of the CFTR modulator ivacaftor/lumacaftor showed a greater clinical effect in improving the functioning of the digestive organs: a decrease in the risk of hyperphosphatasemia and a significant decrease in the number of patients with high levels of gamma-GTP were established, a stable level of liver enzyme activity was noted, and a tendency to increase the activity of pancreatic elastase was revealed. The tendency to decrease the indicators of sweat chlorides is shown. There were no changes in the indicators of respiratory function.